2010
DOI: 10.1021/es902870s
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Energy Demand As Predictor for the Environmental Burden of Commodity Production

Abstract: Cumulative energy demand has been used as a methodology to assess life cycle environmental impacts of commodity production since the early seventies, but has also been criticized because it focuses on energy only. During the past 30 years there has been much research into the development of more complex single-score life cycle impact assessment methodologies. However, a comprehensive analysis of potential similarities and differences between these methodologies and cumulative energy demand has not been carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 356 publications
(173 citation statements)
references
References 33 publications
7
164
0
2
Order By: Relevance
“…Impact assessment was done using the methods Cumulative Energy Demand (CED) v. 1.08 [29,51] (unit: MJ), and Global Warming Potential (GWP) [29,52] (unit: carbon dioxide equivalents, CO 2 eq. ), as implemented in SimaPro [36].…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…Impact assessment was done using the methods Cumulative Energy Demand (CED) v. 1.08 [29,51] (unit: MJ), and Global Warming Potential (GWP) [29,52] (unit: carbon dioxide equivalents, CO 2 eq. ), as implemented in SimaPro [36].…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%
“…While carbon footprint is undoubtedly of high environmental relevance and gives a first important insight into the impact of nutrition on the environment, it is clearly insufficient to describe the full range of environmental impacts of food systems. Some studies assess the use of fossil energy only, which was found to be a good indicator for the total environmental impact in general, but notably with the main exception of agricultural products (Huijbregts et al 2010). Agricultural production has a number of environmental impacts not related to fossil energy use or climate impacts.…”
Section: Challenges For the Environmental Assessment Of Nutritionmentioning
confidence: 99%
“…We conducted an integrated assessment of the net environmental benefits of this transition in WWTPs for more than 50 individual countries to determine how best to update current methods of wastewater treatment and facilitate sustainable WWTPs in various parts of the world. impacts on the environment (16)(17)(18)(19). However, there is increasing recognition that EPMs alone are insufficient.…”
Section: Significancementioning
confidence: 99%